Experiences of Health Professionals Caring for People Presenting to the Emergency Department After Taking Crystal Methamphetamine ("ICE"). (2nd January 2017) - Cleary, Michelle; Jackson, Debra; Woods, Cindy; Kornhaber, Rachel; Sayers, Jan; Usher, Kim
Abstract : Globally, addiction to "ICE" (crystal methamphetamine) is increasing and presents emergency health care services personnel with a number of challenges. This paper reports the first of two major themes arising from a qualitative study investigating health professionals' experiences' managing people presenting to the Emergency Department (ED) after taking "ICE." The theme "Caring for people who use 'ICE' when presenting to EDs" comprises five subthemes. These are: (a) expecting the unexpected: " they're just off their heads" ; (b) complexity of care: " underlying trauma and emotional dysregulation"; (c) connecting and relationships: " engaging in a calm and helpful way" ; (d) coordinating care and teamwork: " keeping them quiet and away from everybody" and (e) learning and reflection: " we need to rethink our treatment options." These findings highlight the complexity and resource-intensity associated with providing emergency care to persons affected by ICE, and the need for thoughtful strategies that can further develop the capacity and capability of health professionals to provide optimal care to people using ICE.